Pharmacy Undergraduates’ Epistemic Cognition and Medication Beliefs as Predictors of Conceptual Learning and Academic Progress - Ilona Sodervik; Leena Hanski; Eero Laakkonen; Nina Katajavuori (Journal of Education in Science, Environment and Health)
The importance of studies showing the impact of students' epistemic beliefs on their conceptual learning and academic progress is increasing. This study investigated pharmacy students’ domain-specific epistemic cognition and topic-specific beliefs related to their level of conceptual prior knowledge, learning and study progress during the first academic year. Data were collected from 125 students using a pre-test/post-test design with a multiple-choice questionnaire, an open-ended case task and a measure of domain-specific epistemic cognition and topic-specific beliefs concerning medication. The results showed that students’ prior knowledge predicted their academic performance and more sophisticated epistemic cognition was related to better conceptual understanding, faster study progress, and fewer anti-medication beliefs. Anti-medication beliefs hindered participants’ success in the case task and were related to weaker study progress. Our study shows that epistemic cognition and topic-specific beliefs play a role in students’ performance, learning, and study progress